Performance evaluation of sulphur oxidizing bacteria (Thiobacillus thiooxidans) on productivity and quality of sunflower (Helianthus annuus L.): Performance evaluation of sulphur oxidizing bacteria (Thiobacillus thiooxidans) on productivity and quality of sunflower (Helianthus annuus L.) - M SENTHIVELU; M ANANDHAM; S HARISH; R SASIKALA (Journal of Oilseeds Research, 2023)
Field experiments were conducted with an objective of assessing the performance of Sulphur Oxidizing Bacteria (SOB) on productivity and quality of sunflower during Kharif and rabi seasons 2021. The results revealed that, application of RDF (60:90:60 kg NPK/ha) + sulphur @ 20 kg/ha with SOB as seed treatment @ 1 kg/ha + soil application @ 1 kg/ha recorded significantly higher value of head diameter (18.6cm), grain/capitulum (1015 Nos.), seed yield (2440 kg/ha), oils content (42.5%), gross return (˂109800/ha), net return (˂54400/ha) and benefit cost ratio (1.98) compared to application of RDF alone and control. However, it was on par with application of RDF + sulphur @ 20 kg/ha combined with SOB as soil application @ 2 kg/ha. From the experimental results, it was concluded that application of RDF (60:90:60 kg NPK/ha) + sulphur @ 20 kg/ha with SOB as seed treatment @ 1 kg/ha and soil application @ 1 kg/ha is an economically viable options to enhance productivity and oil content of the sunflower.